Les aventuriers du rayonnement juridique français au Moyen-Orient - Catherine Fillon (Cahiers Jean Moulin)
French law schools in the Middle East have, from their creation until after the Second World War, operated by using the teaching services of non-accredited doctors of law. The article analyzes the profiles and motivations of these candidates for expatriation, but also the disappointments to which the deliberately organized absence of any status has not failed to expose these informal ambassadors of French legal culture.